2004
DOI: 10.1109/tvlsi.2004.833668
|View full text |Cite
|
Sign up to set email alerts
|

On circuit techniques to improve noise immunity of CMOS dynamic logic

Abstract: Abstract-Dynamic CMOS logic circuits are widely employed in high-performance VLSI chips in pursuing very high system performance. However, dynamic CMOS gates are inherently less resistant to noises than static CMOS gates. With the increasing stringent noise requirement due to aggressive technology scaling, the noise tolerance of dynamic circuits has to be first improved for the overall reliable operation of VLSI chips designed using deep submicron process technology. In the literature, a number of design techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 23 publications
0
52
0
Order By: Relevance
“…It is also observed that the difference in dynamic noise immunity among the keepers are reduced when the input noise duration is extremely small. This is essential for the high performance operation of dynamic logic gates employing the proposed keepers [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also observed that the difference in dynamic noise immunity among the keepers are reduced when the input noise duration is extremely small. This is essential for the high performance operation of dynamic logic gates employing the proposed keepers [6].…”
Section: Resultsmentioning
confidence: 99%
“…However, this goal is not able to be materialized using a single field-effect transistor. It can be shown that I sp I nm has a lower bound of 1 V D V DD for MOS keepers with a monotonic and concave I-V characteristic [6]. In reality, the delay keeper strength I sp is often comparable to, if not greater than, the noise keeper strength I nm , as shown in Fig.…”
Section: Basic Principlementioning
confidence: 97%
“…While these noises always existed, in the past they had little impact on the performance of integrated circuits and were often neglected. It is the unstopped aggressive technology scaling in an effort to continuously improve chip performance and integration level that makes noise play an increasingly important role in comparison with conventional design metrics like area, speed and power consumption [2].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the switching threshold voltage of static CMOS logic gate is typically around half the supply voltage [2] [3]. Therefore, dynamic logic gates inherently have less noise immunity than static CMOS logic gates and are the weak link in a high-performance VLSI chip designed using deep submicron process technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation